Penerapan Undang-Undang Nomor 27 Tahun 2022 Tentang Perlindungan Data Pribadi oleh Kreditur Selaku Pengendali dan Pemroses Data Pribadi Debitur - Prameswari, Yuanita (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2026)
Law Number 27 of 2022 concerning Personal Data Protection provides a sound legal basis for personal data management in Indonesia. This research examines the implementation of debtor data protection by PNM, a creditor that controls and processes personal data. The aim is to evaluate the implementation of procedures in accordance with applicable regulations. News about personal data protection is increasingly vital in the modern era due to the increasing risk of debtor data leaks and misuse. The research method used is empirical juridical, combining a normative approach from laws and regulations with an empirical approach conducted through interviews with PNM, the creditor. The main focus of this study includes the roles and responsibilities of creditors, legal and operational obstacles, and steps in approval, transparency, and fulfillment of personal data subjects' rights. The results indicate that PNM, as a creditor, has implemented company policies related to transparency in data collection, intended use, and processing consent. However, in practice, the results are not always consistent. Obstacles remain, such as a lack of employee insight, system complexity, and a lack of debtor knowledge. Major obstacles also stem from internal and external factors, such as inadequate monitoring and limited debtor awareness. To address this issue, PNM implemented training, outreach, and operational system adjustments. This study emphasized the importance of strengthening regulations and public education to ensure continued data protection.